Multimedia Interface for The Disabled (Mind) Project - McCrindle, R. J.; Admas, R. M. (International Journal of Virtual Reality, 1998)
The Multimedia Interface for the Disabled (MIND) project is concerned with developing a set of guidelines and authoring tools, for use by multimedia developers, to enable them to augment their products to encompass the specific needs of sensory impaired users. This paper presents the ethos behind the project and describes the MIND software prototype developed. The MIND prototype maximises the effectiveness of multimedia information delivery, through the provision of an adaptable and easily navigated user interface, which incorporates access to the augmented multimedia information created with the authoring tools.